The Theological Appropriation of the Old Testament by the New Testament - Black, Matthew 1908-1994 (1986)
To speak, in general terms, of trends in modern biblical study is often to over-simplify; and certainly to claim that there has been, in recent years, a trend away from the traditional classicist or ‘hellenist’ approach to New Testament problems towards a more Hebraic or semitic-centred approach would be to be guilty of the same exaggeration as E. C. Hoskyns in 1930: ‘(There are) grounds for supposing no further progress in the understanding of … Christianity to be possible unless the ark of New Testament exegesis be recovered from its wanderings in the land of the Philistines (sic) and be led back not merely to Jerusalem, for that might mean contemporary Judaism, but to its home in the midst of the classical Old Testament Scriptures — to the Law and the Prophets.’ There is, nevertheless, some truth in A. M. Hunter's later statement: ‘After ransacking all sorts of sources, Jewish and Greek (and, we may add, starting all sorts of “hares”, some of which have not run very well), (scholars) are discovering the truth of Augustine's dictum, “The New Testament lies hidden in the Old, and the Old is made plain in the New”’ (Novum Testamentum in vetere latet, vetus in novo patet).